STRATEGI IMPLEMENTASI ADMINISTRATOR DALAM SCHOOL BUDGETING MANAGEMENT - Navy, Ammar; Fahmi, Agus (Universitas Pendidikan Mandalika, 2023)
Abstract: The activity of allocating funds in the implementation of educational operations is a very complex activity, therefore it requires planned management by competent people. The purpose of this research is to understand and know about the implementation of administration in financial management and school financing. The method used in this research is descriptive qualitative by conducting interviews with the source directly in depth. The results of the research obtained are the problems that often occur in education financing, including limited sources of funds, uneven education funds received from the government, lack of transparency in education financing in schools, and financing that is not managed properly which can be caused by less competent fund managers in schools. The importance of this research lies in the implementation of administrative administration in the financial field of education financing that must be considered by school principals to improve the quality of school administration.Keywords: Administrative Implementation, School Budgeting ManagementAbstrak: Kegiatan mengalokasikan dana pada pelaksanaan operasional pendidikan merupakan kegiatan yang sangat kompleks, oleh karena itu dibutuhkan pengelolaan yang terencana oleh orang-orang yang berkompeten. Tujuan dari penelitian ini adalah memahami dan mengetahui tentang implementasi administrasi dalam manajemen keuangan dan pembiayaan sekolah. Metode yang digunakan dalam penelitian ini adalah Kualittif deskriptif dengan melakukan interview pada sumbernya langsung secara mendalam. Adapun hasil penelitian yang didapat adalah adanya masalah yang sering terjadi dalam pembiayaan pendidikan antara lain sumber dana yang terbatas, tidak meratanya dana pendidikan yang diterima dari pemerintah, kurang transparannya pembiayaan pendidikan di sekolah-sekolah, serta pembiayaan yang tidak dikelola dengan baik yang bisa disebabkan karena kurang kompetennya pengelola dana di sekolah. Pentingnya penelitian ini terletak pada implementasi administrasi tata usaha dalam bidang keuangan pembiayaan pendidikan yang harus diperhatikan oleh kepala sekolah untuk meningkatkan mutu tata usaha sekolah.Kata Kunci: Implementasi Admnistrasi, School Budgeting Management